Between Domestic and Urban Spaces: Preparing for Shabbat in Ashkenazic Communities, 13th-15th Centuries - Lehmann, Ariella (Jewish studies quarterly, 2021)
In 13th to 15th-century Ashkenazi Jewish communities, preparing candles and food not only created a sanctified domestic space for Shabbat, but also required Jews to interact with urban spaces, often shared with Christians. The preparation of Shabbat candles demonstrates the porous boundaries between synagogue and home. The physical, ritual and symbolic aspects of Shabbat candles emphasized their domesticity, especially when viewed against Christian ritual uses of candles. However, Shabbat candles were also present in synagogues symbolically through liturgy and in the reckoning of candle-lighting time. The need to keep food warm over Shabbat without kindling fire demonstrates the importance of urban settings. Jews used urban or communal ovens to insulate food, even when they were able to do so at home. The urban settings of Shabbat preparations reveal how the entire community, regardless of age, gender, and status, fashioned a temporal - but tangible - »Jewish space« between homes, synagogues, streets and ovens.